Factors associated with professional identity among ICU nurses during COVID‐19: A cross‐sectional study - Baoyi Zhang; Hongmei Tao; Minyi Xie; Jingjing Zhang; Meifen Zhang; Yanyan Zhang (Wiley, 2023)
Abstract Aim To determine the associated factors of professional identity among intensive care unit (ICU) nurses during the COVID‐19 pandemic in China. Design Multicentre cross‐sectional study. Methods This study invited 348 ICU nurses in five hospitals in China from May to July 2020. Online self‐report questionnaires were adopted to collect their demographic and occupational characteristics, perceived professional benefits and professional identity. Based on univariate and multiple linear regression analysis, a path analysis was performed to determine the associated factors' effects on professional identity. Results The mean score of professional identity was 102.38 ± 16.46. Perceived professional benefits, doctor recognition level and family support level were associated with ICU nurses' professional identity. The path analysis revealed that perceived professional benefits and doctor recognition level had direct effects on professional identity. In addition, doctor recognition level and family support level had indirect effects on professional identity through the mediation of perceived professional benefits.